Examining and evaluating Entrepreneurship Development and Business Climate in Northern Iraq - Kanabi , Taban; Tasie, George (Advances in Social Sciences Research Journal, 2020)
The study is an examination of the entrepreneurship development and business climate of the Northern part of Iraq. The undertaking of the study stems from insights which exhibit that efforts to foster economic growth and development and other social aspects are influenced by entrepreneurship development. But the major challenge is that such ability and effectiveness rely significantly on an economy’s business climate. This study examines the nature of business climate in North Iraq and how it is influencing entrepreneurship development. The study also examined challenges undermining entrepreneurship development. Opportunity-based and resources-based theoretical insights on entrepreneurship development were used to shed more light on the aspect of and related entrepreneurship development initiatives. This was reinforced by a combination of empirical studies on entrepreneurship development and business climate. Statistical data was also used to support the established arguments and the findings showed that efforts to develop effective entrepreneurship development activities rely on the need to harness between political, economic, social and technological aspects. The findings also showed that political instabilities, lack of capital funding, lack of infrastructure, barriers to entry and the red tap are key determinants of North Iraq’s business climate. The results further led to the conclusion that the business climate in North Iraq is imposing severe limitations on entrepreneurship development.